Chemotherapy-Induced Cognitive Impairment and Neuroaxonal Damage: Investigating the Role of Serum Neurofilament Light Chain - Husni Minanda Fikri; Syafrita, Yuliarni; Lydia Susanti; Syarif Indra; Restu Susanti; Reno Bestari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Chemotherapy-induced cognitive impairment (CICI), colloquially termed "chemobrain," represents a significant challenge for cancer survivors, potentially affecting up to 85% of patients undergoing treatment. Diagnosis often relies on neuropsychological testing and imaging, which may lack sensitivity for early detection or reflect chronic changes. Neurofilament light chain (NfL), a neuronal structural protein released into biofluids upon neuroaxonal damage, emerges as a promising biomarker. This study investigated the relationship between serum NfL levels and the degree of cognitive impairment in patients receiving chemotherapy. Methods: An observational, cross-sectional study was conducted involving 50 cancer patients undergoing chemotherapy at Dr. M. Djamil General Hospital Padang between October and December 2024. Cognitive function was assessed using the Montreal Cognitive Assessment Indonesian version (MoCA-Ina), and depression was screened using the Patient Health Questionnaire-9 (PHQ-9). Serum NfL levels were quantified using an Enzyme-Linked Immunosorbent Assay (ELISA) method. The Kruskal-Wallis test was employed to analyze the relationship between serum NfL levels and cognitive function status (normal, mild impairment, moderate-severe impairment). Results: Cognitive impairment (MoCA-Ina assessed) was identified in 41 (82%) of the 50 participants, with 30 (60%) exhibiting mild and 11 (22%) exhibiting moderate to severe impairment. The median serum NfL level across all subjects was 23.44 pg/ml (range: 13.81-68.71 pg/ml). A statistically significant relationship was observed between serum NfL levels and the presence and severity of cognitive impairment (p = 0.02). Median NfL levels progressively increased from the cognitively normal group (18.49 pg/ml) to the mild impairment group (23.5 pg/ml) and the moderate-severe impairment group (24.5 pg/ml). Post-hoc analysis revealed significant differences in NfL levels between the normal group and both the mild (p=0.03) and moderate-severe (p=0.01) impairment groups. Conclusion: This study demonstrated a significant positive association between serum NfL levels and the presence and severity of cognitive impairment in cancer patients undergoing chemotherapy. These findings support the potential utility of serum NfL as an accessible biomarker for detecting chemotherapy-associated neuroaxonal damage and concomitant cognitive decline.